Investigation of the time-dependent release of plasmid DNA from protamine and dextran sulfate multilayers - Chen, Averil Min Hui (2009)
The layer-by-layer (LbL) technique has aroused great interest in many areas of research, especially in biotechnology. It involves the LbL coating of polyelectrolyte with opposite charges alternatively on a template, to form a product possessing customizable properties and functionalities. Biopolymers and biomolecules are fabricated onto colloid templates to provide biological functions for biopharmaceutical applications such as multifunctional carriers. An example is using the polyelectrolyte multilayer (PEM) coated particles as a DNA carrier by incorporating DNA as a layer in the PEM. The product assists delivery of DNA into the cell, offers protection of DNA during intracellular trafficking and allows controlled release of DNA inside the cell. DNA incorporated in the PEM had been successfully expressed in cells, showing the delivery of intact DNA is achievable using PEM coated particles. The aim of this work is to study the defoliation of protamine and dextran sulfate layers in the cytoplasm through observation of time dependent expression of DNA with respect to its layer depth in the PEM. Silica particles coated with protamine, dextran sulfate and DNA, with varied number of additional layers on top of the DNA layer, were given to HEK293T cells. The decreasing rate of expression of the DNA with increasing layer depth shows defoliation of the multilayer within the cells. This information should be of great value for future studies aiming to functionalize PEM coated particles.